Ouessar, Mohamed - (:unkn) unknown (My University, 2026)
Short Biography of Dr Mohamed OUESSAR Dr. Mohamed Ouessar has a doctorate in Applied Biological Sciences (Land management) from the University of Ghent in Belgium. He is currently a senior researcher at the Arid Zone Research Institute (Institut des Régions Arides) (IRA) (Médenine, Tunisia) and the coordinator of the RS and GIS Unit of his institute. He is serving also as the Responsible for the Training and Capacity Building Section. Since his appointment as researcher at IRA in 1994, he has contributed actively, as coordinator or team member, to the realization of numerous joint research projects funded by national and international agencies (WB, ABOS, EU, CSFD, UNU, USDA, UNESCO, etc.). His research programs focused mainly on water harvesting, GIS based hydrological modeling and decision support systems, impact assessment, watershed management, climate change impacts and adaptation, combating desertification and drylands management. He contributed also to the training and capacity building through supervision of trainees and students of all levels from national and international centers and organizations and universities, part time teaching at the universities on drylands and natural resources management related issues, and organization of specialized local and international training sessions. He has been solicited to provide expertise for studies and/or projects conducted by national (Ministries of Agriculture, environment, planning) and international organizations (FAO, GTZ, OSS, UNU) in addition to the assistance of the local development agencies (agriculture, environment, development). He published several scientific papers in national and international journals (over 30) in addition to his contribution to the edition of books and book chapters. He is also reviewer for several international journals. He is affiliated to several international professional associations: IUSS, Réseau Erosion (IRD), Réseau Télédétection (AUF, France), BPD (UK), IGU (Commission on Land Degradation and desertification). He is also volunteering to many NGOs operating in his region (ASNAPED, UTAIM, AAMTT, etc.).